An Emotionally Intelligent, Ecolinguistic Approach to Content and Language Integrated Learning - Edward Rutledge; Marni Manegre (Anglica. An International Journal of English Studies)
This article examines the incorporation of concepts derived from ecolinguistics and social-emotional learning (SEL) into the content and language integrated learning (CLIL) methodology when teaching about climate change in the second language classroom. A test of this approach was implemented during a teaching practicum with 14- and 15-year-old students in Catalonia to survey their beliefs, attitudes, and knowledge of the topic before and after experiencing content-based lessons on climate change. Findings suggest that such an approach may be effective, if not essential, for fostering communicative competence, subject matter learning, and social-emotional resilience when presenting challenging existential issues in the classroom.